Actions of Jurisprudents in Helleh Related to the propagation of Islamic Culture after Mongol Attack - mahdieh mahdavi kani (تاریخ اسلام)
The ignorance of viewpoints and the reactions of religious scholars and jurisprudents in the diverse social domains has led to the less criticism and investigation of their measures, approaches and actions and this great inheritance is less accessible to the elites and social actors in the later centuries. Considering the actions of religious jurisprudents and scholars specially in some periods of the past when the Islamic society was suffering from the crises and challenges is of great significance. The ignorance of these historical-social researches made the religious centers and institutions be unconcerned towards the conditions and the cultural-social consequences of social actions. Taking advantage of the library sources and descriptive-analytical approach, this article is to answer the problem on the grounds applied in the domain of religious culture by the jurisprudents of Helleh in the 7th and 8th centuries, when the world of Islam was seriously affected by Mongolian attack and the collapse of Abbasid caliphate. The results of research clarify that the endeavors of jurisprudents have been toward facilitating the cultural relations, changing the religious conflicts into the scientific negotiations, putting emphasis on ethics as the foundation of Islamic culture, taking cultural responsibility, avoiding from passive readings in the domain of religious culture and taking advantage of the cultural templates in the domain of propagating the culture and religious instructions